2016
DOI: 10.1016/j.earscirev.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprinting and tracing the sources of soils and sediments: Earth and ocean science, geoarchaeological, forensic, and human health applications

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
126
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(127 citation statements)
references
References 228 publications
(245 reference statements)
0
126
1
Order By: Relevance
“…Establishing the relative proportions of modern and historic contaminant sources is not straightforward Owens et al 2016). Principal component analysis (PCA) has been applied to discriminate be-tween natural and anthropogenic sources of contaminants in urban environments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Establishing the relative proportions of modern and historic contaminant sources is not straightforward Owens et al 2016). Principal component analysis (PCA) has been applied to discriminate be-tween natural and anthropogenic sources of contaminants in urban environments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of variance was conducted to test if five sources could be separated by each of 10 remaining colour fingerprint properties. According to the MixSIAR model, the property values of sediment data should fall within the range of the source data, the so-called "range-test" (Owens et al 2016;Collins et al 2017). All 45 possible pairwise plots from the 10 colour fingerprint variables indicated that only G, L, X, and Y met this requirement.…”
Section: Colour Coefficient Selectionmentioning
confidence: 99%
“…In brief, soil and sediment samples were air-dried and sieved through a 63 μm screen as the majority of actively transported sediment in this watershed is dominated by fine particles <63 μm (D. Lobb, unpublished data) and as this is the size fraction typically analysed in most sediment source fingerprinting studies (Walling 2013;Owens et al 2016;Collins et al 2017). The reflectance spectra were then determined using a diffuse spectroradiometer (ASD FieldSpec Pro, Analytical Spectral Device Inc., CO, USA).…”
Section: Determination Of Colour Coefficientsmentioning
confidence: 99%
See 2 more Smart Citations